Total factor productivity and its determinants in Poland - evidence from manufacturing industries: The role of ICT - Marcin Kolasa; Zbigniew Żółkiewski (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
The aim of the paper is total factor productivity (TFP) analysis in Poland and identification of its determinants. In the first part, TFP growth in Poland is calculated. Following the growth literature, TFP is frequently interpreted as the level of technology and effectiveness of its use. In the remaining sections, the authors try to identify the factors determining TFP growth in Poland. The analysis is carried out on a panel of manufacturing industries over the period of 1994-2001. The determinants of TFP can be divided into four groups. First of all, TFP in Poland grows as a result of convergence, which can be explained by the transfer of technology from more technologically developed countries. Another factor accelerating TFP growth is the innovativeness of domestic enterprises, which can be approximated by expenditures on R&D. Transition reforms had also a positive impact on TFP growth in Poland in the analysed period, by increasing the effectiveness of the production factors use. Finally, ICT investment is found to contribute positively to TFP growth as well.
Keywords: 330; Produktivität; Informationstechnik; Polen